Functional Outcome of Cemented Bipolar Hemiarthroplasty in Patients with Fracture Neck of Femur - Reddy, Pinnamareddy Bhargava; Kandhasamy, Vivek; Christin I, Shebin; K, Praveen; S, Gokul (Journal of Neonatal Surgery, 2025)
Background: Femoral neck fractures are common injuries in the elderly, often resulting from low-energy trauma. These fractures are associated with significant morbidity and mortality due to underlying comorbidities and prolonged immobilization. Cemented bipolar hemiarthroplasty is a preferred treatment for displaced intracapsular fractures in this population, aiming to restore mobility and reduce complications. Objective: This study evaluates the functional outcomes and postoperative recovery in patients undergoing cemented bipolar hemiarthroplasty for fracture neck of femur (NOF), with particular attention to the influence of age, sex, surgical timing, and complication rates. Methods: A prospective, hospital-based study was conducted over one year at the Department of Orthopaedics, Vinayaka Missions Kirupananda Variyar Medical College and Hospital, Salem. Thirty patients aged above 55 years with displaced NOF fractures underwent cemented bipolar hemiarthroplasty. Functional outcomes were assessed using the Modified Harris Hip Score (HHS) at multiple postoperative intervals (2 weeks, 6 weeks, 3 months, and 6 months). Statistical analyses included Chi-square tests and ANOVA, with significance set at p<0.05. Results: The majority of patients were aged 61–80 years, with a slight male predominance. Functional outcomes showed consistent improvement, with mean HHS increasing from 41.40 postoperatively to 88.25 at six months (p<0.0001). At final follow-up, 66.7% of patients had excellent outcomes, and 26.7% had good outcomes. Complication rates were low (16.7%), with minor issues such as radiolucency and prosthetic subsidence observed. No major complications like dislocation or infection were reported. Conclusion: Cemented bipolar hemiarthroplasty offers excellent functional recovery and low complication rates in elderly patients with intracapsular femoral neck fractures. Early surgical intervention and structured rehabilitation significantly enhance postoperative outcomes, supporting this procedure as a reliable treatment option for active, elderly individuals